Understanding Lay Counselor Perspectives on Mobile Phone Supervision in Kenya: A Mixed Method Study (Preprint) - Noah S. Triplett; Clara Johnson; Sharon Kiche; Kara Dastrup; Julie Nguyen; Alayna Daniels; Anne Mbyawo; Cyrilla Amanya; Sean Munson; Pamela Y. Collins; Bryan J. Weiner; Shannon Dorsey (2022)
BACKGROUND Task-shifting is an effective mode of increasing access to mental health treatment via lay counselors with less specialized training that deliver care under supervision. Mobile phones may present a low-tech opportunity to replace or decrease reliance on in-person supervision in task-shifting, but important technical and contextual limitations must be examined and considered. OBJECTIVE Guided by human-centered design methods, we aimed to understand how mobile phones are currently used when supervising lay counselors, determine the acceptability and feasibility of mobile phone supervision, and generate solutions to improve mobile phone supervision. METHODS Participants were recruited from a large hybrid effectiveness-implementation study in western Kenya, wherein teachers and community health volunteers have been trained to provide trauma-focused cognitive behavioral therapy. Lay counselors (N=24) and supervisors (N=3) participated in semi-structured interviews in the language of the participants choosing (i.e., English or Kiswahili). The participants included high frequency, average frequency, and low frequency phone users in equal parts. Six lay counselors (25%) did not have smart phones. These participants were all CHVs, and split across high frequency (n=2) and low frequency users (n=4). Interviews were transcribed, translated when needed, and analyzed using thematic analysis. Themes were compared across frequency of phone use following a mixed methods data transformation and integration approach. RESULTS Uses included: clinical updates, scheduling and coordinating, and supporting research procedures. Participants liked how mobile phones decreased burden, facilitated access to clinical and personal support, and enabled greater independence of lay counselors. Participants disliked how mobile phones limited information transmission, limited relationship building between supervisors and lay counselors, and disrupted communication flows. Mobile phone supervision was facilitated by access to working smart phones, ease and convenience of mobile phone supervision, mobile phone literacy, and positive supervisor-counselor relationships. Limited resources, technical difficulties, communication challenges, and limitations on which activities can effectively be performed via mobile phones were barriers to mobile phone supervision. Lay counselors and supervisors generated 27 distinct solutions to increase the acceptability and feasibility of mobile phone supervision. Differences emerged in specific themes pertaining to acceptability and feasibility by frequency of use. CONCLUSIONS Researchers considering how digital technology can be used to increase mental and digital health equity must consider limitations to implementing digital health tools and design solutions alongside end-users to increase acceptability and feasibility. CLINICALTRIAL NA. Study procedures were previously published in: https://doi.org/10.1186/s43058-020-00102-9 INTERNATIONAL REGISTERED REPORT RR2-https://doi.org/10.1186/s43058-020-00102-9